PENGARUH PEMBERIAN PENGUATAN TERHADAP MOTIVASI BELAJAR SISWA KELAS V SDN 018 RANTAU SIALANG KECAMATAN KUANTAN MUDIK KABUPATEN KUANSING - Yulia Citra; Syahrilfuddin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2019)
This research was motivated by the weak learning motivation of students in the teaching and learning process, which was indicated by students’ passive behavior and lack of enthusiasm. The purpose of this study was to determine whether there was an effect of reinforcement on students’ learning motivation and to identify the magnitude of its influence. This study employed a quantitative approach with an experimental research type, using a pre-experimental design. The pre-experimental design applied was the one-group pretest–posttest design. The subjects of this study were 27 fifth-grade students of SDN 018 Rantau Sialang, consisting of 8 male students and 19 female students. The variables in this study were reinforcement and students’ learning motivation. Data were collected through documentation and questionnaires. The validity test used the Pearson product-moment formula, while the reliability test used the Alpha formula. The prerequisite analysis test employed a normality test using the Kolmogorov–Smirnov One-Sample test with SPSS 17.0 for Windows. Hypothesis testing was conducted using the t-test with the assistance of SPSS, followed by an effect size test. The results showed that reinforcement had a significant effect on students’ learning motivation, as indicated by the t-test results at significance levels of 1% and 5%, namely tcount > ttable, at the 1% level (7.751 > 1.298) and at the 5% level (7.751 > 1.674). The calculation of the effect size obtained an ES value of 3.146, which was categorized as high because the effect size exceeded 0.8. It can be concluded that reinforcement had a significant effect on the learning motivation of fifth-grade students at SDN 018 Rantau Sialang, Kecamatan Kuantan Mudik, Kabupaten Kuantan Singingi, with a high effect category.